2019
DOI: 10.3390/plants8050113
|View full text |Cite
|
Sign up to set email alerts
|

Selenium in Germinated Chickpea (Cicer arietinum L.) Increases the Stability of Its Oil Fraction

Abstract: Selenium is an essential mineral in human nutrition. In order to assess its effect on the stability of chickpea oil, seeds were germinated and tested with different amounts of sodium selenite (0.0, 0.5, 1.0 and 2.0 mg/100g seeds) for four days. Oil was extracted from sprouted chickpea and its physical properties, fatty acid profile (FAME), oxidative stability index (OSI), lipase and lipoxygenase (LOX) activities, cellular antioxidant activity (CAA), and phenolics and carotenoids were assessed and compared to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Lazo-Vélez et al (2018) also found that the addition of sodium selenite could improve the selenium content of germinated soybeans. Increases of selenium during seeds germination were detected in other cereals seeds, such as chickpea (Guardado-Félix et al, 2019), brown rice (Liu & Ning, 2021), and rice (Oryza sativa L) (Yin et al, 2019).…”
Section: Introductionmentioning
confidence: 98%
“…Lazo-Vélez et al (2018) also found that the addition of sodium selenite could improve the selenium content of germinated soybeans. Increases of selenium during seeds germination were detected in other cereals seeds, such as chickpea (Guardado-Félix et al, 2019), brown rice (Liu & Ning, 2021), and rice (Oryza sativa L) (Yin et al, 2019).…”
Section: Introductionmentioning
confidence: 98%
“…The cellular antioxidant activities (CAA) of bound and free phenolics extracted from flour and tortillas were evaluated using the protocol described by Guardado‐Félix, Serna Saldivar, Gutiérrez‐Uribe, & Chuck Hernandez () with slight modifications as follows: Human colorectal adenocarcinoma cells (CaCo‐2) were seeded in a 96‐well microplate (1 × 10 4 –1 × 10 5 cells/well) and used when reaching their exponential growth phase. After incubation for 24 hr, the cell culture medium was discarded and the cells gently washed with 100 µl of PBS (37°C).…”
Section: Methodsmentioning
confidence: 99%
“…A previous study found that application of selenite led to a higher accumulation of selenium in sprouts compared to selenate, which probably results from the faster incorporation of selenite into organic Se compounds in comparison with selenite [22]. The germination of chickpea and soybean sprouts under the treatment of selenite increased the amounts of carotenoids and isoflavones, such as daidzein, genistein, and glycitein, as compared to those in non-selenized sprouts [23][24][25]. The application of Se increased the total phenol contents in coriander and tatsoi microgreens by 21% and 95%, respectively [26].…”
Section: Introductionmentioning
confidence: 91%